Sastra propaganda - Wasono, Sunu (Jakarta : Wedatama Widya Sastra, 2008)
On Indonesian modern literature
Daftar pustaka : p. 177-180
Keywords: Indonesian literature -- History and criticism; Propaganda -- Indonesia; Politics and literature -- Indonesia